2023
DOI: 10.1101/2023.02.18.525405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Domestic dogs maintain positive clinical, nutritional, and hematological health outcomes when fed a commercial plant-based diet for a year

Abstract: Objective: Domestic dogs can maintain health on complete and well-balanced canine plant-based nutrition (K9PBN). Novel insight on health outcomes in dogs consuming K9PBN is of relevance to veterinary professionals and consumers given a growing interest in non-traditional dog foods with perceived health benefits, while considering potential safety concerns. We aimed to investigate nutritional equivalence by measuring clinical health outcomes in adult dogs fed K9PBN over twelve months compared to a meat-based di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…However, a sizeable and rapidly-growing body of evidence has now shown that both dogs and cats can thrive on nutritionally-sound vegan diets. Such results are evident within both canine (nine studies: [16][17][18][19][20][21][22][23][24]) and feline (four studies: [23,[25][26][27]) studies of health outcomes. Furthermore, their behavioural needs and welfare are not compromised by such diets [28].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, a sizeable and rapidly-growing body of evidence has now shown that both dogs and cats can thrive on nutritionally-sound vegan diets. Such results are evident within both canine (nine studies: [16][17][18][19][20][21][22][23][24]) and feline (four studies: [23,[25][26][27]) studies of health outcomes. Furthermore, their behavioural needs and welfare are not compromised by such diets [28].…”
Section: Discussionmentioning
confidence: 98%
“…A considerable body of recent evidence indicates that provided such diets are formulated to be nutritionally-sound, as modern commercial vegan diets usually are [15], dogs and cats maintained on vegan diets can have longevity and health at least equivalent, and in some respects superior, to those maintained on conventional meat-based diets. Such results are evident within studies of health outcomes in both dogs (nine studies: [16][17][18][19][20][21][22][23][24]) and cats (four studies: [23,[25][26][27]). Dietary palatability also appears equivalent overall [28].…”
Section: -mentioning
confidence: 97%